DARI MESIR HINGGA ALJAZAIR: JALAN PANJANG DIPLOMASI INDONESIA MENUJU KONFERENSI ASIA AFRIKA KEDUA (1955-1965) - Ayu Wulandari (Handep: Jurnal Sejarah dan Budaya, 2022)
This research discusses Indonesian diplomatic role in pursuing the implementation of the Second Asian-African Conference (AAC) in 1965 in Algeria. This study is motivated by the limited historiography highlighting Indonesian central role in encouraging the implementation of the second conference. In fact, organizing the conference was one of the Indonesian Government efforts to repeat the success of the first Asian-African Conference in Bandung in 1955. The national political interests were also the reason behind this diplomatic effort. This research used historical method with archive, magazine, and newspaper as sources. This study aims to analyze the Government’s efforts, challenges, and the social and political conditions. The results show that Indonesia had initiated and prepared the second conference for almost a decade (1955-1965). The venue had even changed for several times: from Egypt to Algeria. Despite a long diplomatic process, this conference was canceled due to the unfavorable regional and international political situation. The novelty of this study is Indonesian diplomatic patterns and actions towards the implementation of the Second AAC, such as personal diplomacy efforts, political safaris, and diplomatic meetings.